PEMANFAATAN WAHANA DRONE TIPE QUADCOTER DJI PHANTOM 3 ADVANCE UNTUK PEMETAAN AREAL KAMPUS POLITEKNIK PERTANIAN NEGERI SAMARINDA - Musa Kun Firdaussy; Dyah Widyasasi (Politeknik Pertanian Negeri Samarinda, 2017)
This research is motivated because currently remote sensing technology continues to develop, both in terms of data collection and processing. This is indicated by the existence of data collection techniques using unmanned aircraft for mapping aerial photographs. The advantage of using this technology is that it is effective and efficient in terms of both time and human resources for mapping in areas that are not too large. Another advantage is that it can produce clearer photos, because the plane's flying height is below 400 meters above ground level so that the shooting process does not experience cloud disturbances. The purpose of this research is to make an aerial photo map at the State Agricultural Polytechnic of Samarinda, to validate objects in aerial photographs and in the field, and to provide information about the area, boundaries, and topography in the area of ​​the Samarinda State Agricultural Polytechnic campus. The implementation of activities and research objects is the area of ​​the Samarinda State Agricultural Polytechnic campus. In this study, a small format aerial photo mapping method with a Quadcopter was used, making it easier to determine the place to start flying (take off) and landing (landing). With Quadcopter rides, runway problems are no longer an obstacle. The results showed that the shooting carried out with a Quadcopter vehicle at an altitude of 200 m above the ground resulted in an area of ​​28.17 ha and a spatial resolution of 8.40 cm / pixel. The results of validation in aerial photographs and in the field using drones have a small difference between 0-4 cm with an average of 1.625 cm / photo. From the results of digitizing campus objects, there are 30 objects on campus with a total area of ​​2.67 hectares. As for the topography results in the campus area, the highest point is 107.5 meters above sea level and the lowest point is 60 meters above sea level.